(untitled) (Revista Innova Educación, 2019)
Attitudes are ways in which an individual is actively adapted to their environment and is the result of a cognitive, affective and behavioral process, attitudes are the result of learning to respond to stimuli, and are manifested in the form of positive or negative tendency towards people, objects and situations, in this way the objective of the study was to determine environmental attitudes to environmental problems in students, 4th grade of secondary education in the city of Puno, during the 2016 academic year. The methodology used corresponds to the simple descriptive type and the diagnostic design with quantitative and qualitative data, 232 students were taken as a population, the study sample consisted of 132 students, selected through non-probabilistic sampling, to whom a survey that allowed identifying the positive and negative environmental attitudes of the students. The results were that 58% of the students in the total have a positive attitude with respect to environmental care, concluding that the students have a favorable attitude, means that in them there is responsibility, care towards environmental problems.